2022
DOI: 10.2196/32626
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Growth Hormone Treatment Using a Connected Device in Latin America: Real-World Exploratory Descriptive Analysis Study

Abstract: Background Recombinant human growth hormone (rhGH) therapy is an effective treatment for children with growth disorders. However, poor outcomes are often associated with suboptimal adherence to treatment. Objective The easypod connected injection device records and transmits injection settings and dose data from patients receiving rhGH. In this study, we evaluated adherence to rhGH treatment, and associated growth outcomes, in Latin American patients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Our data confirmed low adherence in aGHD population on rhGH treatment (6). Mean adherence in the whole population was nearly 73% after two years of observation, far inferior to those of pediatric population collected by the ECOS studies (15)(16)(17)(18)(19)(20). This could be explained given the different treatment results gained in pediatric versus aGHD: on one hand, height gain is an evident and…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our data confirmed low adherence in aGHD population on rhGH treatment (6). Mean adherence in the whole population was nearly 73% after two years of observation, far inferior to those of pediatric population collected by the ECOS studies (15)(16)(17)(18)(19)(20). This could be explained given the different treatment results gained in pediatric versus aGHD: on one hand, height gain is an evident and…”
Section: Discussionsupporting
confidence: 70%
“…Koledova et al confirmed the indication in children with short stature treated with rhGH, as the value is related to better growth outcomes (18). Meanwhile, other studies chose 85% as the threshold for "good adherence", and 56% as the threshold for inadequate adherence (20). As above stated, noncompliance is one of the most important causes of chronic treatment failure.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have examined the prevalence of nonadherence among children and adolescents with clinical indications for r-hGH treatment, including GHD, Turner syndrome, small for gestational age (SGA), and chronic renal failure (CRF), and reported that up to 71% and 82% of children and adolescents, respectively, were nonadherent to their treatment (1,9). Poor adherence to the r-hGH treatment negatively affects both long-term clinical outcomes (leading to suboptimal growth outcomes) (9,(11)(12)(13)(14) and healthcare system cost and resources (10,(15)(16)(17)(18). Living with GHD can be both physically and emotionally challenging for the patient and their family (11,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%